Poligami di Indonesia: Apakah Sejalan dengan Nilai-nilai Pancasila dan Hukum Nasional? Polygamy in Indonesia: Is it in Line with the Values of Pancasila and National Law? - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Wahyu Sugiyanto; Ahmad Baihaqi; Habib Rahadian (LITERA: Jurnal Ilmiah Mutidisiplin, 2024)
This research explains the conformity of polygamy practices in Indonesia with Pancasila values and national law, with the aim of assessing how far polygamy is in accordance with the state’s basic principles and applicable legal regulations. This research approach uses qualitative methods by studying cases and analyzing documents. Data was collected through interviews with key informants, observations of court cases, and analysis of legal documents and academic literature. Research findings show that although polygamy is regulated by Law no. 1 of 1974 concerning Marriage, practices are often inconsistent with Pancasila values, especially in terms of social justice and gender equality. Weak legal implementation and inadequate protection of the rights of first wives and children contribute to exacerbating injustice. This research recommends legal reform, strengthening supervision, and protecting women’s rights to increase compatibility between the practice of polygamy and the basic principles of state and national law.